(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This study examines the experiences of health insurance policyholders in Mysore City, exploring factors influencing satisfaction, challenges faced, and expectations from insurance providers. Through a survey of policyholders, the research investigates service quality dimensions, including claims processing, communication, and support. The findings highlight key areas for improvement, such as reducing claims processing times, enhancing transparency, and providing personalized support. The study's insights can inform health insurance providers' strategies to enhance policyholder satisfaction, build trust, and improve loyalty in Mysore City.